Physiotherapy treatment in children with obstructive bronchitis and prolonged cough - N. A. Geppe; S. I. Shatalina; N. A. Krylova; V. S. Malyshev (Сеченовский вестник)
The article considers the problems of treatment of the children with obstructive bronchitis and prolonged cough with physiotherapy methods.